2008
DOI: 10.1242/jeb.013771
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence and biological activity of a calcitonin-like diuretic hormone (DH31) from Rhodnius prolixus

Abstract: SUMMARYDiuresis in the blood-gorging hemipteran Rhodnius prolixus is under neurohormonal control and involves a variety of processes and tissues. These include ion and water movement across the epithelium of the crop and the Malpighian tubules, and muscle contractions of the crop, hindgut and dorsal vessel, which facilitate mixing of the blood-meal, mixing of the haemolymph, as well as the expulsion of waste. One of the neurohormones that might play a role in this rapid diuresis belongs to the calcitonin-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…The Midgut Junction DH31 expressing cells express and require the peptide hormone gene Dh31 for this peristalsis. While previous work in Drosophila has shown that DH31 can stimulate urine secretion from the Malpighian tubules though the activation of a cAMP pathway [4,68], topical application of DH31 has been shown to stimulate contractions in the hindgut and dorsal vessel of the blood sucking insect Rhodnius prolixus [69]. Although this data suggests that DH31 stimulates visceral muscle motility whether this peptide hormone directly activates this contraction remains to be tested.…”
Section: Discussionmentioning
confidence: 94%
“…The Midgut Junction DH31 expressing cells express and require the peptide hormone gene Dh31 for this peristalsis. While previous work in Drosophila has shown that DH31 can stimulate urine secretion from the Malpighian tubules though the activation of a cAMP pathway [4,68], topical application of DH31 has been shown to stimulate contractions in the hindgut and dorsal vessel of the blood sucking insect Rhodnius prolixus [69]. Although this data suggests that DH31 stimulates visceral muscle motility whether this peptide hormone directly activates this contraction remains to be tested.…”
Section: Discussionmentioning
confidence: 94%
“…(1) Brown et al, 1999; (2) Rohwedder et al, 2015; (3) Mercer et al, 2011; (4) Schoofs et al, 1993; (5) Siviter et al, 2000; (6) Nässel et al, 1998; (7) Holzer and Holzer-Petsche, 1997; (8) Hökfelt et al, 2001; (9) Coast et al, 2001; (10) Johnson et al, 2005; (11) Brugge et al, 2008; (12) LaJeunesse et al, 2010; (13) Vanderveken and O'Donnell, 2014; (14) Sternini, 1991; (15) Kendig et al, 2014; (16) Rattan and Tamura, 1998; (17) Anselmi et al, 2005; (18) Kaminski et al, 2002; (19) Veenstra, 2009; (20) Corleto, 2010; (21) Farhan et al, 2013; (22) Veenstra and Ida, 2014; (23) Ren et al, 2015; (24) Sano et al, 2015; (25) Takizawa et al, 2005; (26) Sterkel et al, 2012; (27) Chen et al, 2015; (28) Carlsson et al, 2013; (29) Slade and Staveley, 2016; (30) Bhatt and Horodyski, 1999; (31) Duve et al, 2000; (32) Rankin et al, 2005; (33) Audsley et al, 2008; (34) Heinonen et al, 2008; (35) Duve et al, 1994; (36) Audsley and Weaver, 2009; (37) Dockray, 2009.…”
Section: Figurementioning
confidence: 99%
“…Interestingly, serotonin is colocalized with a calcitonin-related DH, Rhopr-DH 31 , and Rhopr-DH is colocalized with a kinin-like DH, Rhopr-K (Te Brugge et al 2001, 2005, 2008). However, neither Rhopr-DH 31 nor Rhopr-K can stimulate absorption across the AMG (V. A. Te Brugge, personal communication), and neither is very active at stimulating secretion by the upper MTs.…”
Section: Neuroendocrine Control Of Fluid Transport In a Blood-gorgingmentioning
confidence: 99%